Forest significant and conservation among the Semaq Beri tribe of orang asli in Terengganu State, Malaysia - Ramle Abdullah; Greg Acciaioli; Nur Hafizah Ramle; Mohd Sukhairi Mat Rasat (2014)
The Orang Asli are an indigenous ethnic group found in peninsular